Worksets expand the scholarly utility of digital libraries - Page, K; Jett, J; Cole, T; Kudeki, D; Bainbridge, D; Organisciak, P; Stephen Downie, J (Association for Computing Machinery, 2018)
Scholars using digital libraries and archives routinely create worksets—aggregations of digital objects—as a way to segregate resources of interest for in-depth scrutiny. To illustrate how worksets can enhance the scholarly utility of digital library content, we distill from prior user studies three key objectives for worksets (extra-digital library manipulation, intra-itemproperties, and robust representations), and discuss how they motivated the workset model being developed at the HathiTrust Research Center (HTRC). We describe how HTRC’s implementation of its RDF-compliant workset model helps to satisfy these objectives.